The Effect Of Dryland Exercise Training: Analysis Of 100-Meter Freestyle Swimming Speed Ability In Bima Tirta Ngawi Athletes - Ali Munir; Zahara Zahwa Ayesha; Yusuf Panjiantariksa; Fantas Setyadi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Swimming is one of the achievement sports that demands physical ability, technique, and optimal biomotor condition. Athletes are required not only to have good swimming technique but also muscle strength, explosive power, coordination, and anaerobic endurance that support performance while swimming. This study aims to determine the effect of Dryland Exercise training on 100-meter freestyle swimming speed ability in Bima Tirta Ngawi athletes. The method used in this study was a pre-experimental one group pretest and posttest design. The research location was conducted at the Bima Tirta Ngawi Swimming Club. The researcher selected athletes from the swimming branch of sports to be the research population. The sample used consisted of 8 athletes, comprising 5 males and 3 females, using a total sampling technique. The test instrument used in the study was the 100-meter freestyle swimming speed test. This study used observation techniques as a data collection method and employed descriptive analysis and t-test for data analysis, with calculations using IBM SPSS version 29. The study results showed an effect of Dryland Exercise training on 100-meter freestyle swimming speed with a tcount value of 14.607 > ttable 3.556 and a significance value of 0.000 < 0.005. The hypothesis in this study is stated as accepted, with results indicating a significant effect of Dryland Exercise training on the 100-meter freestyle swimming speed ability of Bima Tirta Ngawi athletes